3D Heterogeneous Device Arrays for Multiplexed Sensing Platforms Using Transfer of Perovskites. Issue 30 (17th June 2021) - Jang, Jiuk; Park, Young‐Geun; Cha, Eunkyung; Ji, Sangyoon; Hwang, Hyunbin; Kim, Gon Guk; Jin, Jungho; Park, Jang‐Ung
Abstract: Despite recent substantial advances in perovskite materials, their 3D integration capability for next‐generation electronic devices is limited owing to their inherent vulnerability to heat and moisture with degradation of their remarkable optoelectronic properties during fabrication processing. Herein, a facile method to transfer the patterns of perovskites to planar or nonplanar surfaces using a removable polymer is reported. After fabricating perovskite devices on this removable polymer film, the conformal attachment of this film on target surfaces can place the entire devices on various substrates by removing this sacrificial film. This transfer method enables the formation of a perovskite image sensor array on a soft contact lens, and in vivo tests using rabbits demonstrate its wearability. Furthermore, 3D heterogeneous integration of a perovskite photodetector array with an active‐matrix array of pressure‐sensitive silicon transistors using this transfer method demonstrates the formation of a multiplexed sensing platform detecting distributions of light and tactile pressure simultaneously. Abstract : By using a removable polymer film, transfer of perovskite arrays to planar or nonplanar surfaces is realized. The total thickness of the fabricated perovskite device is thin enough to form conformal contact on various surfaces with 3D geometries. This work provides the integration of perovskites on contact lenses and pressure sensors, achieving multiplexed sensing platforms for future electronics.